Investigation of transport and magnetic properties of SiC/Cu diluted magnetic semiconductor nano-multilayer films. (September 2016) - Sun, Ning; Li, Chunjing; Fu, Yuting; Li, Yanghua; Bu, Dechong; An, Yukai; Liu, Jiwen
Abstract: The SiC/Cu nano-multilayer films were deposited on Si substrates using radio frequency and direct current alternative sputtering technique. In this paper, the transport and magnetic properties of the films were investigated. XRR shows the SiC/Cu periodical structures of the films. XRD confirms that the 3C-SiC crystal structure is formed in the films without heating substrates. The XPS indicates that the Cu atoms substitute for Si sites of the SiC lattice and exist in a mixed valance state of Cu + and Cu 2+ . The best fitting for the plots of ln ρ versus T −1/4 using the combination of the Mott and the band gap VRH models suggests that the carriers in the films are strongly localized. The films have a typical semiconductor characteristic and an obvious room temperature ferromagnetism which should arise from the bond magnetic polarons. The maximum values of saturation magnetization and carrier concentration are up to 15.2 emu/cm 3 and 1.86E + 22/cm 3 respectively. Highlights: SiC/Cu nano-multilayer film was deposited on Si substrate by RF and DC alternative sputtering. 3C-SiC crystal structure is formed in the films without heating substrates. Cu + /Cu 2+ substitutes for Si site of SiC and increase of SiC thickness changes conduction type. Films have a typical semiconductor characteristic and an obvious RT ferromagnetism. Maximum values of Ms and pc are up to 15.2 emu/cm 3 and 1.86E + 22/cm 3 respectively.